Nikah Dini Dari Berbagai Tinjauan: Analisis Kombinasi Tematik dan Holistik - Nasution, Khoiruddin (Sunan Kalijaga State Islamic University & The Asia Foundation, 2009)
The negative effect of child marriage is one of the historical background of the promulgation of marriage law of Indonesia no. 1 of 1974 and its government regulation. Howwever, the ultimate goal of the promulgation of the law seems never able to achieve. The main reason of the failure is always argument that the Indonesian marriage law is not accordance with Islamic marriage law. The article tries to prove that child marriage is only possible for the prophet Muhammd Saw not for his followers. This possibility only for the prophet therefore is a kind of exceptional regulation. The conclusion is based basically on al-Qur an and sunna of the prophet from a number of perspective and combination of thematic and holistic analysis and approach.